Reconstruction of nasal defects using the Rieger flap - Filipe Lopes Decusati; Antônio Egidio Rinaldi (Revista Brasileira de Cirurgia Plástica)
Introduction: the reconstruction of skin defects in the distal part of the nose is always a challenge. The dorsal nasal flap, initially described by Gillies, was unveiled when Rieger, in 1967, described the use of a modified rotation flap that used the redundant skin of the glabella to repair full-thickness defects of the lower half of the nose of equal or greater size of 2 cm, allowing reconstruction in a single surgical time. Methods: A retrospective study was carried out, selecting patients who had basal cell carcinoma, in the middle and/or lower third of the nose, who were treated at the Plastic Surgery outpatient clinic of the Plastic Surgery Service Prof. Dr. Oswaldo de Castro, in the period from 2017 to 2019. Results: The total number of patients was six, with ages ranging from 64 to 95 years, with an average of 80.67 years. Five of these patients were male, with only one female. There were no complications during or after the procedures. Also, there were no cases of infection, bleeding, hematoma, dehiscence, or necrosis of the flap. Conclusion: the Rieger flap is a good option for cases of reconstruction of defects located in the lower half of the nose; it is performed in a single moment, is easy to perform, and has a high level of patient satisfaction. It provides an adequate result aesthetics of the reconstructed area, in texture and color, through the use of specific tissues for the nasal covering.